2018
DOI: 10.1136/heartjnl-2017-312384
|View full text |Cite
|
Sign up to set email alerts
|

National, regional and global mortality due to alcoholic cardiomyopathy in 2015

Abstract: The variation of ACM mortality burden is greater than for other alcohol-attributable diseases, and partly may be the result of stigma and lack of detection. Misclassification of ACM fatalities is a systematic phenomenon, which may be caused by low resources, lacking standards and stigma associated with alcohol-use disorders. Clinical management may be improved by including routine alcohol assessments. This could contribute to decrease misclassifications and to provide the best available treatment for affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…Согласно последним эпидемиологическим данным, алкоголь вносит существенный (6,3%) вклад в общее количество случаев смерти от КМП. Выявлена значительная гетерогенность уровня смертности от АКМП: в России отмечаются наибольшие значения данного показателя (163,8 случая на 1 млн населения в год), существенно превышающие аналогичные цифры для большинства других стран и регионов [10]. Причиной отличий в эпидемиологии АКМП может являться разный характер употребления спиртосодержащих напитков в отдельных странах, например, частота запойного потребления алкоголя [5,11].…”
Section: эпидемиологияunclassified
See 1 more Smart Citation
“…Согласно последним эпидемиологическим данным, алкоголь вносит существенный (6,3%) вклад в общее количество случаев смерти от КМП. Выявлена значительная гетерогенность уровня смертности от АКМП: в России отмечаются наибольшие значения данного показателя (163,8 случая на 1 млн населения в год), существенно превышающие аналогичные цифры для большинства других стран и регионов [10]. Причиной отличий в эпидемиологии АКМП может являться разный характер употребления спиртосодержащих напитков в отдельных странах, например, частота запойного потребления алкоголя [5,11].…”
Section: эпидемиологияunclassified
“…К тому же, имеют место недостаточное сообщение об указанной патологии в качестве причины смерти (примерно в каждой второй стране мира), а также вынесение неправильных суждений (до двух третей зарегистрированных случаев) о наличии и степени выраженности АКМП. Это обусловлено низкой частотой выполнения аутопсий во многих странах, cтигматизацией лиц с алкогольной интоксикацией, а также отсутствием четких диагностических критериев для верификации данного заболевания [10,12].…”
Section: эпидемиологияunclassified
“…A study based on individual‐participant data for nearly 0.6 million consumers showed that even low alcohol consumption was associated with disease risks (Wood et al., ). Alcoholic cardiomyopathy (ACM) is characterized by myocardial degeneration caused by long‐term drinking, which causes the ventricle to dilate, and manifests as cardiac dysfunction (Iacovoni et al., ; Manthey et al., ; Rodrigues et al., ). Approximately one‐half of all cases of dilated cardiomyopathy are reported to be caused by alcohol (George and Figueredo, ; Li et al., ; Weintraub et al., ).…”
mentioning
confidence: 99%
“…In their  Heart  paper, Manthey  et al  published disturbing findings on the worldwide mortality due to alcoholic cardiomyopathy (ACM), incorporating data from death registries for more than 100 countries 7. In 2015, there were more than 27 000 deaths from ACM and this translated into close to 8% of all global deaths from cardiomyopathy being caused by alcohol.…”
mentioning
confidence: 99%